Ruins of the past, ruins of the future: Nostalgia and late-industrial imaginaries in Sicily - D'Orsi, Lorenzo (L'Uomo Società tradizione sviluppo, 2024)
Based on ethnographic research conducted between 2020 and 2022 in the town of Gela, Sicily, this paper examines the transformation of urban imaginaries. In the 1960s, the establishment of the Eni petrochemical plant transformed Gela from a small rural village into a symbol of industrialization in southern Italy, bringing a newfound sense of centrality and vanguard to the town. However, the recent closure of the plant has resulted in depopulation, environmental pollution, the proliferation of illegal constructions, and an uncertain future. This article analyzes the process of ruination that characterizes the industrial ruins and the urban landscape of Gela, marked by abandoned buildings, unfinished projects, and incomplete developments. On the one hand, it investigates inhabitants’ attempt to make invisible this decaying materiality and reimagine their city. On the other hand, it demonstrates how the narratives around these ruins of modernity shape a sense of intimacy and locality. This landscape of ruins is also intertwined with the emergence of new social imaginaries rooted in nostalgia for Gela’s rural past and the remnants of its ancient Greek colony. These imaginaries overshadow the industrial era and establish a new sense of place more aligned with the tourism paradigm. Ultimately, this paper reveals how the new rural and pre-industrial imaginary, and the related aspirations of economic renaissance, are supported by the very sense of grandeur conveyed by that petrochemical plant that people today wish to remove.